2011
DOI: 10.1074/jbc.m110.188193
|View full text |Cite
|
Sign up to set email alerts
|

Single Domain Intracellular Antibodies from Diverse Libraries

Abstract: Interfering intracellular antibodies are valuable for biological studies as drug surrogates and as potential macromolecular drugs per se. Their application is still limited because of the difficulty of acquisition of functional intracellular antibodies. We describe the use of the new intracellular antibody capture procedure (IAC 3 ) to facilitate direct isolation of functional single domain antibody fragments using four independent target molecules (LMO2, TP53, CRAF1, and Hoxa9) from a set of diverse libraries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…All our previous attempts to produce recombinant LMO2 protein have proved unsuccessful due to the intransigent insolubility of the protein in induction systems (unpublished). However, we found that co-expressing LMO2 with the anti-LMO2 single domain resulted in efficient production of soluble protein that was readily purified and crystallized in the dimeric state35. This has two main implications.…”
Section: Discussionmentioning
confidence: 99%
“…All our previous attempts to produce recombinant LMO2 protein have proved unsuccessful due to the intransigent insolubility of the protein in induction systems (unpublished). However, we found that co-expressing LMO2 with the anti-LMO2 single domain resulted in efficient production of soluble protein that was readily purified and crystallized in the dimeric state35. This has two main implications.…”
Section: Discussionmentioning
confidence: 99%
“…Camelid VHH intrabodies have a higher probability of correct intracellular folding, although they do contain cysteines that can form disulfide bonds (Colby et al ., 2004b; Saerens et al ., 2005). The method that is designed to directly select for stable intrabodies in a high-throughput manner is intracellular antibody capture, which uses an in situ two-hybrid screen to select for antigen-scFv interactions within the cytoplasm of yeast (Auf der Maur et al ., 2001; Colby et al ., 2004c; Feldhaus et al ., 2003; Tanaka et al ., 2011; Visintin et al ., 1999). Alternatively, the antigen-binding complimentary determining regions of an unstable scFv can theoretically be “loop- grafted” into several well-characterized intrabody consensus scaffolds that are reported to exhibit improved intracellular folding and stability (Ewert et al ., 2004).…”
Section: Selection and Engineering Methodsmentioning
confidence: 99%
“…However, initial screening generally reveals valuable lead candidate intrabodies for therapeutic or mechanistic studies that can be further characterized in situ (Kvam et al ., 2010). Another method that is designed to directly select for intrabodies that recognize intracellular conformers of target proteins in context is intracellular antibody capture, which uses an in situ two-hybrid screen to select for antigen-scFv interactions within the cytoplasm of yeast or within mammalian cells (Auf der Maur et al ., 2001; Feldhaus et al ., 2003; Tanaka et al ., 2011; Visintin et al ., 1999). …”
Section: Introduction To Intrabodiesmentioning
confidence: 99%
“…The stability and functionality of independent VHs is maintained also when they are expressed as intrabodies [32,33]. …”
Section: Introductionmentioning
confidence: 99%